2010
DOI: 10.1016/j.nuclphysa.2010.04.010
|View full text |Cite
|
Sign up to set email alerts
|

Charged-particle thermonuclear reaction rates: III. Nuclear physics input

Abstract: The nuclear physics input used to compute the Monte Carlo reaction rates and probability density functions that are tabulated in the second paper of this series

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
350
4
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(374 citation statements)
references
References 137 publications
19
350
4
1
Order By: Relevance
“…The dashed lines are the astrophysical S-factor arising from interference combinations giving the highest and lowest values in the astrophysical region based on the parameters recommended by Iliadis et al [21]. The addition of the predicted subthreshold J π = 1/2 + state [5] significantly enhances the S-factor, as shown by the solid lines.…”
Section: Figmentioning
confidence: 88%
See 1 more Smart Citation
“…The dashed lines are the astrophysical S-factor arising from interference combinations giving the highest and lowest values in the astrophysical region based on the parameters recommended by Iliadis et al [21]. The addition of the predicted subthreshold J π = 1/2 + state [5] significantly enhances the S-factor, as shown by the solid lines.…”
Section: Figmentioning
confidence: 88%
“…The impact of such a state is illustrated in Figure 4, where the astrophysical S-Factor most recently recommended by Iliadis et al [21] is shown (dashed lines), together with same S-factor modified by the inclusion of the proposed subthreshold 1/2 + state with parameters as suggested by [5] (solid lines). The two curves shown in each case correspond to the highest and lowest S-factors allowed due to the uncertainty in the interference between the 38 and 665 keV J π = 3/2 + states.…”
Section: Figmentioning
confidence: 96%
“…V. In the case of nova thermometers, the ratios O/S, S/Al, O/P, and P/Al have a pronounced temperature dependence, but are also strongly dependent on the uncertain rate of the 30 P(p,γ ) 31 S reaction. This reaction also affects the precision of the mixing meter Si/H.…”
Section: A Probing Classical Novae -Nuclear Thermometers and Mixing mentioning
confidence: 94%
“…Further measurements regarding the off-resonant and on-resonant higher energy range, were done in order to improve our knowledge of levels in the 19 F compound nucleus that are relevant to nuclear astrophysics and to complete available data known in literature [7], [8], [9].…”
Section: Introductionmentioning
confidence: 99%